Purification, characterization, and molecular cloning of the xylanase from Streptomyces thermovulgaris TISTR1948 and its application to xylooligosaccharide production - Pinpanit Boonchuay (2018)
© 2016 Elsevier B.V. All rights reserved. A crude xylanase preparation from Streptomyces thermovulgaris TISTR1948 was able to hydrolyze KOH-treated corncob and to produce bioactive xylooligosaccharides (XOs). A thermostable cellulase-free endo-xylanase from strain TISTR1948 was purified 15.0-fold from the crude preparation, with a recovery yield of 13.0%. On SDS-PAGE, the purified enzyme had an apparent molecular mass of 46.2 kDa. The N-terminal and internal amino acid sequences were determined and the cloned xylanase gene were sequenced. The 1434-bp gene encodes a protein with a predicted molecular mass of 46,976 Da. The deduced amino acid sequence had a high degree of identity with the sequences of GH 10 xylanases from Streptomyces spp. The purified xylanase was highly stable within a pH range of 4.0-11.5 and was thermostable within a temperature range of 50-70°C. The activity of the enzyme reached a maximum at 65°C; the enzyme's half-life was 90 min at 70°C. Enzymatic activity was enhanced in the presence of metal ions, Ca2+, Co2+, and Mn2+but almost completely inhibited by Hg2+, Pb2+, and SDS. The Kmand Vmaxvalues of the enzyme with beechwood xylan as the substrate were 37.6 μM and 303 U/mg, respectively. The crude, partially purified, and purified xylanases were assayed for XO production from KOH-treated corncob. The main component of the XO products was xylobiose, with very little xylose and arabinose. An in vitro evaluation of XOs from the purified xylanase showed that they enhanced the growth of probiotic Lactobacillus plantarum TISTR1465.